2022
DOI: 10.1093/eurheartj/ehac085
|View full text |Cite
|
Sign up to set email alerts
|

QRS micro-fragmentation as a mortality predictor

Abstract: Aims Fragmented QRS complex with visible notching on standard 12-lead electrocardiogram (ECG) is understood to represent depolarization abnormalities and to signify risk of cardiac events. Depolarization abnormalities with similar prognostic implications likely exist beyond visual recognition but no technology is presently suitable for quantification of such invisible ECG abnormalities. We present such a technology. Methods and results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The predictive value of QRS-T angle was reported additive to HRV-based risk stratification ( Poulikakos et al, 2018 ) in a multivariate analysis of the follow-up cardiac events and mortality in a population of end-stage renal disease patients on haemodialysis. QRS-T angle was also reported predictive of mortality in atrial fibrillation patients who had an automatic cardioverter-defibrillator implanted for primary prophylactic reasons ( Hnatkova et al, 2022 ). At the same time, however, our observations of the absence of any clearly measurable time lag between heart rate changes and QRS-T angle changes, while in agreement with previous observations of rapid changes ( Hnatkova et al, 2010 ), are somewhat at odds with the report by Kenttä et al (2010) who described hysteresis-type differences between RR interval changes and QRS-T angle changes during exercise testing in a relatively small study of healthy volunteers undergoing exercise testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The predictive value of QRS-T angle was reported additive to HRV-based risk stratification ( Poulikakos et al, 2018 ) in a multivariate analysis of the follow-up cardiac events and mortality in a population of end-stage renal disease patients on haemodialysis. QRS-T angle was also reported predictive of mortality in atrial fibrillation patients who had an automatic cardioverter-defibrillator implanted for primary prophylactic reasons ( Hnatkova et al, 2022 ). At the same time, however, our observations of the absence of any clearly measurable time lag between heart rate changes and QRS-T angle changes, while in agreement with previous observations of rapid changes ( Hnatkova et al, 2010 ), are somewhat at odds with the report by Kenttä et al (2010) who described hysteresis-type differences between RR interval changes and QRS-T angle changes during exercise testing in a relatively small study of healthy volunteers undergoing exercise testing.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Physiology frontiersin.org an automatic cardioverter-defibrillator implanted for primary prophylactic reasons (Hnatkova et al, 2022). At the same time, however, our observations of the absence of any clearly measurable time lag between heart rate changes and QRS-T angle changes, while in agreement with previous observations of rapid changes (Hnatkova et al, 2010), are somewhat at odds with the report by Kenttä et al (2010) who described hysteresis-type differences between RR interval changes and QRS-T angle changes during exercise testing in a relatively small study of healthy volunteers undergoing exercise testing.…”
Section: Figure 12mentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study, Hnatkova et al showed that QRS microfragmentation, which is imperceptible to the human eye, is strongly related to death. 18 In addition, previous close observations of ECGs have shown that subtle abnormalities increase the risk of ventricular arrhythmias. 19,20 The AI model developed in the present study may automatically detect these complexes and subtle ECG abnormalities.…”
Section: Performance Evaluationmentioning
confidence: 99%